Role of Family Business in India and Impact of Financial Strategies: Exploring the Evolution and Challenges of Family Businesses in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
For three generations and beyond the article tends to examine the path of family business in India. Over the years, family companies have faced many obstacles, and the position of leadership has moved from internal leadership to the integration of external family business leaders. The paper starts with a brief on the past and essence of family business in India, accompanied by the problems of external business leaders and their incorporation. The essay would also discuss why family-owned firms want to make the move to work professionally, and how the performance of the transition is influenced by possessing sufficient motives. We would also discuss what makes effective and unsuccessful methods, evaluate the problems associated and offer recommendations for better practice.